ISOLASI DAN IDENTIFIKASI FUNGI MIKORIZA ARBUSKULAR DARI PERAKARAN TEBU (SACCHARUM OFFICINARUM L) DI AREA PERKEBUNAN TEBU SEI SEMAYANG KABUPATEN DELI SERDANG - Ahmad Shafwan S Pulungan (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2015)
Research isolation and identification of arbuscular mycorrhiza fungi was conducted in March 2009. The purpose of this study was to determine the genus of the arbuscular mycorrhizal roots tebu.Sampling contained in an area measuring 20m x 20m with a 5 point sampel.Teknik taking isolate spores used in arbuscular mycorrhiza is a technique castings strain and followed by centrifugation techniques . The observations obtained 8 types of arbuscular mycorrhiza spores comprising 7 species of the genus Glomus and one type of the genus Acaulospora .